TINJAUAN STATUS MANGIFERA LAURINA DAN KERABATNYA - Fitmawati Fitmawati (PTTI, 2006)
Fitmawati. 2006. Taxonomic Status of Mangifera laurina and its Related Species. Floribunda 3(2): 29-37.-This study is aimed to investigate the taxonomic status of species related to M. laurina, to find out whether they represent a natural species or should be placed in several different species. The result showed that morphological phylogenetic analysis supported the idea for separating three monophyletic species (M. laurina, M. aplanata, M. lalijiwa), considering that M. rubropetala and M. indica are synonym, and defining two independent lineages of sister group (i.e. the clade of M. lalijiwa and the clade consist of M. indica, M. laurina, M. aplanata and M. rubropetala). Morphologically, M. lalijiwa is characterized by having glomerulate and glabrous inflorescence and tips of petal ridge free of the surface. In contrast, the other species usually posseses non-glomerulate and puberulous inflorescence and base or a half of base of petal ridge at free of the surface. Phylogenetic analysis of E-RAPD was incongruent with that of morphological analysis. However, the molecular phylogeny support whether that M. aplanata is separated from other species and that cultivars of M. lalijiwa are a monophyletic group.